Suplementasi Asam Folat Meningkatkan Kadar Hemoglobin dan Indeks Eritrosit pada Wanita Usia Subur - Fatikhah Intan Maharani; Lucia Sincu Gunawan; Rumeyda Chitra Puspita (Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: Women of reproductive age (WORA) are a group prone to anemia, one of which is due to folic acid deficiency which plays a role in DNA synthesis and erythrocyte formation.Objective: The study aimed to determine the differences in hemoglobin and erythrocyte indices among women of reproductive age with folic acid supplementation.Methods: A quasi-experimental research on the design of one group pretest-posttest on 67 female students of Setia Budi University was conducted in October 2024–February 2025. Respondents aged 18-25 years, selected by purposive sampling, were given folic acid tablet supplement (Folavit® 0.4 mg) twice daily for 14 days. Primary data were obtained from hematology examinations taken before after the intervention with a hematology analyzer, showing changes in hemoglobin and erythrocyte indices. Test Wilcoxon Signed Rank to analyze the data.Results: The results showed significant increases in hemoglobin from 12.96 ± 0.93 g/dL to 13.53 ± 0.91 g/dL (p<0.001), MCV from 85.54 ± 4.36 to 86.39 ± 4.14 (p<0.001), MCH from 27.61 ± 2.12 pg to 28.20 ± 2.06 pg (p<0.001), and MCHC from 33.05 ± 1.62% to 33.74 ± 1.56% (p<0.001) after folic acid supplementation.Conclusion: Folic acid supplementation increased hematological status and may serve as a preventive strategy against anemia in women of reproductive age.